2016
DOI: 10.1161/circulationaha.115.019341
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Hsd11b2 in the Brain Causes Salt Appetite and Hypertension

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…For example, deletion of the mineralocorticoid receptor in SMC in mice results in hypotension and protection from Ang II-induced pressor responses (24). Hypertension in apparent mineralocorticoid excess syndrome has been presumed to be caused by sodium retention in the distal nephron, but recent studies showed that deletion of the gene encoding 11β-hydroxysteroid dehydrogenase type 2 (11βHSD2) specifically in the brain caused increased salt sensitivity causing salt-sensitive hypertension independent of alterations in renal sodium excretion or fluid retention (25). The phenotype in S-CUL3Δ9 mice described herein demonstrates a plausible vascular mechanism contributing, at least in part, to severe early-onset hypertension seen in PHAII patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, deletion of the mineralocorticoid receptor in SMC in mice results in hypotension and protection from Ang II-induced pressor responses (24). Hypertension in apparent mineralocorticoid excess syndrome has been presumed to be caused by sodium retention in the distal nephron, but recent studies showed that deletion of the gene encoding 11β-hydroxysteroid dehydrogenase type 2 (11βHSD2) specifically in the brain caused increased salt sensitivity causing salt-sensitive hypertension independent of alterations in renal sodium excretion or fluid retention (25). The phenotype in S-CUL3Δ9 mice described herein demonstrates a plausible vascular mechanism contributing, at least in part, to severe early-onset hypertension seen in PHAII patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hsd11b2 in the murine brain triggers a central drive to consume salt (Evans et al, 2016). The rat Hsd2KO model offers a more robust platform to investigate the physiological mechanisms of central versus renal-centric salt sensitivity than is feasible in the mouse.…”
Section: Models Of Hypertensive Renal Damagementioning
confidence: 99%
“…Thus, reduced 11-HSD2 activity in the brain does not intrinsically cause hypertension, but it promotes salt hunger and salt sensitivity. The authors suggested that 11-HSD2-positive neurons integrate salt appetite and the blood pressure response to dietary sodium through a mineralocorticoid receptor-dependent pathway [76]. …”
Section: Functional Roles Of 11-hsd2mentioning
confidence: 99%